Застосування діагностичних маркерів ротової рідини в ранній діагностиці стоматологічної захворюваності в працівників сталепромислових підприємств - Самойленко, А. В.; Павлов, Сергій Васильович; Возна, Ірина Володимирівна; Samoilenko, A. V.; Pavlov, S. V.; Vozna, I. V. (Українська медична стоматологічна академія, 2018)
Мета роботи – проаналізувати спеціалізовану наукову літературу для узагальнення даних про сучасні погляди на використання біологічних маркерів для ранньої діагностики стоматологічних захворювань у працівників зі шкідливими умовами праці. Матеріали і методи. Проаналізували і вивчили доступну наукову літературу за останні роки, присвячену особливостям поширеності стоматологічних захворювань серед працівників підприємств зі шкідливими умовами праці та використанню біологічних маркерів для їх ранньої діагностики. Висновки. Отже, аналіз літературних даних продемонстрував можливість використання біологічних маркерів у стоматології як малоінвазивного, інформативного методу діагностики і скринінгу ефективності стоматологічного лікування. Удосконалення списку біомаркерів ротової рідини залежить від їхньої стабільності й точності виявлення, включаючи чутливість і відтворюваність аналізів, простоту їх виконання, високу чутливість та специфічність. Цель работы - провести анализ специализированной научной литературы для обобщения данных о современном взгляде на использование биологических маркеров для ранней диагностики стоматологических заболеваний у работников с вредными условиями производства. Материалы и методы. Проанализировали и изучили доступную научную литературу за последние годы, которая посвящена особенностям распространенности стоматологических заболеваний среди работников предприятий с вредными условиями труда и использованию биологических маркеров для их ранней диагностики. Выводы. Таким образом, анализ литературных данных показал возможность использования биологических маркеров в стоматологии в качестве малоинвазивного, информативного метода диагностики и скрининга эффективности стоматологического лечения. Усовершенствование списка биомаркеров ротовой жидкости зависит от их стабильности и точности выявления, включая чувствительность и воспроизводимость анализов, простоту их выполнения, высокую чувствительность и специфичность. The dental health of the industrial enterprises’ workers has specific differences from the average indicators of the epidemiological examinations, which is associated with a negative effect on the tissue and oral cavity of the working zone’s atmosphere. Under prolonged exposure of the low concentrations of harmful substances, i.e, due to the chronic intoxication in the oral cavity can occur as a disease of the mucous membrane, as well as the disease of hard tissues of the teeth. Despite the presence of measures on the occupational safety and accident prevention protection, the industrial environment of the enterprises is an extreme condition for workers, which requires the further development of effective comprehensive methods of the prevention and the treatment of the major dental diseases. The aim of the work is to carry out the analysis of the specialized scientific literature for the data generalization about modern looks to the use of biological markers for early diagnostics of dental diseases in workers with harmful working conditions. Materials and methods. We have analyzed and studied the available scientific literature in the last years, which is devoted to the peculiarities of the dental diseases’ spread among the workers of the enterprises with harmful working conditions and the biological markers’ use for their early diagnostics. Up until recently the use of mouthwash in diagnostic aims was complicated, that is explained by the following: a barrier of hematosalivation, low level of determination, complication of exposure, it is studied not enough, the indexes got not always correlate with such in plasma of blood, and also absence of attention to methodology of collection and storage of tests of this material to realization of analysis. These problems were largely removed as a result of careful study of physiology of salivary glands, development of sensible methods of amplification, methodology of separation and treatment of standards. The last achievements in diagnostics were conditioned by new molecular approaches. The development of new therapeutic methods is impossible without the establishment of the diagnostic monitoring system to determine the predictors of the disease, its biological markers, criteria for assessing its course, prediction of the possible outcomes and the effectiveness of the therapeutic measures. Researches are actively conducted the last decades in relation to character of content of markers of bone fabric, oxidative and nitrosative stresses, proteins of endogenous cytoprotection cytoprotection (HSP -, HIF, squirrel Klotho), markers of inflammation in a mouthwash at various stomatological diseases. It is known that 99% of organic molecules, that circulate in plasma, identified in saliva and represent the "regional orientation" of pathobiochemical processes. Conclusions. Thus, the analysis of literary data showed possibility of biological markers, using in Dentistry as minimum aggressive, informing diagnostic method and screening of dental efficiency of treatment. Improving the list of saliva biomarkers depends on their stability and accuracy of detection, including the sensitivity and reproducibility of the analyzes, their simplicity of the execution, high sensitivity and specificity.
The diagnostic markers’ application of the oral liquid in the early diagnostics of the dental mobidity in the staff of the steel-manufacturing enterprises’ employees
Keywords: шкідливі чинники виробництва; ротова рідина; біологічні маркери; вредные факторы производства; ротовая жидкость; биологические маркеры; harmful factors of the production; mouthwash; biological markers